An interesting case of CYBB mutation in a Malay boy with normal maternal dihydroxidation test and matched mother-child haplotype. - Ismail, Intan Hakimah; Zainal Abidin, Mohd Azri; Mohamed Nashrudin, Khairoon Nisa (2024)
A 6-month-old Malay boy, second born to non-consanguineous parents, presented with persistent fever, multiple pustular skin lesions and failure to thrive. He had indurated BCG site with pustular discharge within the first 2 months of life. Examination showed multiple pustules and crusted scabs over the face, trunk and lower limbs, fungal lesion at perineum, left cervical, submandibular and axillary lymphadenopathy and hepatosplenomegaly. Despite antibiotics, the affected lymph nodes became suppurative and perineal abscess with discharging sinus developed. Contrast enhanced computed tomography of neck showed retropharyngeal and parapharyngeal collections with locoregional extension. He underwent intra-oral incision and drainage and left submandibular node biopsy. Pus culture grew Staphylococcus haemolyticus, Klebsiella pneumoniae and Escherichia coli from retropharyngeal, lymph node and perineal abscesses, respectively. GeneXpert MTB was positive on axillary lymph node. All lymphocyte subsets were increased. Immunoglobulin panel showed raised IgG, IgA and IgM. Dihydrorhodamine123 (DHR) test revealed impaired neutrophil oxidative burst in response to mitogen. The diagnosis of chronic granulomatous disease (CGD) was made. Anti-tuberculosis was commenced.